Physical activity, cardiovascular health, quality of life and blood pressure control in hypertensive subjects: randomized clinical trial - Arija, Victoria; Villalobos, Felipe; Pedret, Roser; Vinuesa, Angels; Jovani, Dolors; Pascual, Gabriel; Basora, Josep (Health and quality of life outcomes, 2018)
Background Physical activity (PA) promotes cardiovascular health and health related quality of life (HRQoL), although the effect of that on blood pressure (BP) control has rarely been studied in hypertensive subjects. Our aim was to evaluate the effectiveness of a PA intervention programme on cardiovascular disease (CVD) risk, HRQoL and BP control in hypertensive subjects. Methods A randomized clinical trial, with a PA intervention programme of 9 months duration, comprising a walking group of 120 min/week, supervised, and with socio-cultural activities. Participants were 207 hypertensive subjects (68.2 years, 76.8% women). PA (IPAQ-s), diet, CVD risk, BP, BMI, smoking, and HRQoL (SF-36) were assessed at baseline and at the end of the intervention. Changes in CVD risk and in HRQoL during the intervention was calculated (end-baseline score). Multivariate models were applied. Results In multivariate models, the PA intervention programme, with no modification of the diet, decreased CVD risk (− 1.19 points) and the systolic BP (− 8.68 mmHg), and increased some areas of HRQoL (4.45 to 14.62 points). An increase in the percentage of subjects with controlled BP was observed by the PA programme itself (OR 5.395 to 5.785 according to multivariate models), and by the changes during the intervention in the decrease in CVD risk (OR 0.609) and in the increase in the HRQoL in physical component summary (OR 1.041), role physical (OR 1.010), and bodily pain (OR 1.014), independently of controlled BP at baseline. Conclusions This PA intervention programme improved cardiovascular health and HRQoL, and favoured BP control in primary care users with hypertension. Trial registration Clinicaltrials.gov ID NCT02767739 ; Trial registered on May 5th, 2016. Retrospectively registered.